2011
DOI: 10.1016/j.brat.2011.03.002
|View full text |Cite
|
Sign up to set email alerts
|

Postnatal debriefing: Have we thrown the baby out with the bath water?

Abstract: Postnatal debriefing is offered by 78% of maternity services in the UK despite little evidence from randomised controlled trials (RCTs) that it is effective. RCTs in this area have applied debriefing as a prophylactic to all or high risk women, rather than as a treatment for women who request it. This pragmatic trial therefore evaluated existing postnatal debriefing services that provide debriefing as a treatment for women who request it. Forty-six women who met criterion A for posttraumatic stress disorder (P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
30
0
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 32 publications
(33 citation statements)
references
References 27 publications
0
30
0
2
Order By: Relevance
“…Two studies conducted universal interventions (Priest, Henderson, Evans, & Hagan, 2003;Selkirk et al, 2006), and six reported findings from studies (including one longitudinal follow-up), which targeted interventions either according to a perception of trauma (Gamble et al, 2005;Meades, Pond, Ayers, & Warren, 2011) or mode of birth (Kershaw, Jolly, Bhabra, & Ford, 2005;Ryding, Wirén, Johansson, Ceder, & Dahlström, 2004;Small, Lumley, Donohue, Potter, & Waldenström, 2000;Small, Lumley, & Toomey, 2006). One study (Lavender & Walkinshaw, 1998) did not provide a universal intervention, but did not target interventions for individuals potentially at higher risk for PTS or depression after childbirth (e.g., due to perception of trauma or instrumental delivery).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Two studies conducted universal interventions (Priest, Henderson, Evans, & Hagan, 2003;Selkirk et al, 2006), and six reported findings from studies (including one longitudinal follow-up), which targeted interventions either according to a perception of trauma (Gamble et al, 2005;Meades, Pond, Ayers, & Warren, 2011) or mode of birth (Kershaw, Jolly, Bhabra, & Ford, 2005;Ryding, Wirén, Johansson, Ceder, & Dahlström, 2004;Small, Lumley, Donohue, Potter, & Waldenström, 2000;Small, Lumley, & Toomey, 2006). One study (Lavender & Walkinshaw, 1998) did not provide a universal intervention, but did not target interventions for individuals potentially at higher risk for PTS or depression after childbirth (e.g., due to perception of trauma or instrumental delivery).…”
Section: Resultsmentioning
confidence: 99%
“…Of these, two targeted interventions for women who perceived childbirth as traumatic (Gamble et al, 2005;Meades et al, 2011) and one provided an intervention for women following normal vaginal birth (Lavender & Walkinshaw, 1998). Two of these studies provided the intervention shortly after birth (first point of contact within 72 h; Gamble et al, 2005;Lavender & Walkinshaw, 1998) and one provided the intervention at the mother's request (median 16 weeks after birth; Meades et al, 2011). Of the three studies reporting efficacious results, one used a structured CISD approach (Gamble et al, 2005), and two used an unstructured approach (Lavender & Walkinshaw, 1998;Meades et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Le débriefing par un tiers doit être formalisé [32] et peut constituer une aide (réduction du sentiment de dépréciation) mais ne semble pas réduire les symptômes de la dépression [33].…”
Section: Comment L'éviter Ou Le Prévenir ?unclassified